Ciencia intercultural: enseñanza de las reacciones químicas en grado octavo en dialogo con los saberes propios de la comunidad Misak. - Quintero Cano, Sol Alejandra (Góndola, enseñanza y aprendizaje de las ciencias, 2025)
It is undeniable that cultural diversity in Colombia is as broad as its biodiversity; however, Western science has been epistemologically structured from Eurocentric foundations, limiting the possibility of recognizing the world from other subjectivities. In this study, a virtual learning object (OVA) was designed and implemented as a didactic strategy with an intercultural approach, integrating the knowledge of the Misak community from the Las Delicias Botanical Garden with the teaching of chemical reactions in eighth grade at New Cambridge School in Cali. The degree of recognition that students demonstrated towards this knowledge after the learning experience was also analyzed. Through a qualitative methodology based on school ethnography, an interview was conducted with a knowledge holder from the Misak community, whose contributions informed the design of the OVA. The didactic strategy was later implemented with a focus group of students. The OVA made it possible to integrate the knowledge shared in the interview with the teaching of chemical reactions, linking identity elements of the Misak community with processes such as combustion and the chemical interactions between mordants and natural dyes. The implementation provided students with the opportunity to recognize this knowledge and generated interest in the Misak community from an intercultural perspective that fostered positive relations, although without questioning the epistemic violence exercised by Western science. The findings highlight that chemistry teaching with an intercultural approach should be more frequently incorporated into school curricula to recognize the diversity of knowledge systems and reduce epistemic violence and discrimination in educational contexts.